Analysis of pediatricians’ knowledge about autism - Kılınçel, Şenay; Baki, Fikriye (Journal of Surgery and Medicine, 2021)
Background/Aim: In autism spectrum disorders (ASD), early diagnosis is important for treatment, and pediatricians are health professionals who are likely to encounter ASD at the earliest stages. In this study, we aimed to examine the information sources of pediatricians, their current knowledge about autism and the affecting factors. Methods: The study was conducted as an online cross-sectional self-report questionnaire and the data of 145 pediatricians were analyzed. The sociodemographic information form created by the researchers and the Healthcare Professionals’ Knowledge of Childhood Autism Questionnaire-Turkish Version were filled by the participants. Correct response rates were divided into quantile values and under 3rd Quartile (Q3) was considered “insufficient information.” Logistic regression analysis was used for descriptive data and factors affecting the level of knowledge. Results: Of 145 participants, 59.3% completed Child and Adolescent Psychiatry (CAP) internship during their medical education, 60.7% completed CAP rotation, and 49.7% attended training or meetings related to autism. The highest rate of correct answers in autism knowledge evaluation questionnaire was on "Information on social interaction," while the lowest rate of correct answers was on "Information on neurodevelopmental diseases." For the total correct answer rates, the Q3 and Q1 values were 68.1% and 89.5%, respectively. According to the logistic regression model, being single (Mean: 3.60) and not having an MCS rotation (Mean: 8.49) predicted a score below Q3. Conclusions: Our research shows that in this disorder, where early diagnosis is of foremost importance, pediatricians who regularly monitor children have a high level of knowledge about recognizing autistic symptoms; however, there are some deficiencies in answering questions that will resolve the concerns of families about autism. For this reason, pediatricians who examine a child at least 3-4 times a year need pediatric psychiatry training that will give them specific skills in diagnosing and making recommendations, as well as initiating interventions. Another option is being more involved in departments that will enable them to gain experience in autism.